Supporting the UN SDGs transition: Methodology for sustainability assessment and current worldwide ranking - Lorenza Campagnolo; Fabio Eboli; Luca Farnia; Carlo Carraro (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
This analysis lies in the stream of research related to the quantitative assessment of the Sustainable Development Goals (SDGs), adopted by the United Nations at the end of September 2015. We assemble a composite multi-dimensional index and a worldwide ranking of current sustainability. This makes it possible to assess the strengths and weaknesses of today's socio-economic development, as well as environmental criticalities worldwide. The methodology goes through the following steps: screening of indicators capable of addressing the UN's SDGs; data collection from relevant sources; organization into three pillars of sustainability (economy, society, and environment); normalization to a common metrics; aggregation of the 26 indicators into composite indices by pillars as well as in a multi-dimensional index. The final ranking includes 139 countries. Sweden, Norway and Switzerland are at the top of the ranking.
Keywords: O44; O57; Q01; 330; Sustainable Development Goals; Composite Index; Indicators